MENILAI KESEHATAN BANK RAKYAT INDONESIA BERDASARKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING AND CAPITAL) - Rahmawati, Disa; Puspa, Rani; Nurasiah, Iis (Yayasan Education and Social Center, 2024)
This research aims to evaluate the health of Bank Rakyat Indonesia (BRI) in facing global challenges in the banking industry. The RGEC method is used to measure bank health during the 2016-2020 period. The results show that Bank BRI as a whole is in good health. In the increasingly fierce competition in the banking industry, it is important for banks to maintain their existence with optimal performance. Bank health assessment is crucial in ensuring the bank's ability to face risks, implement good corporate governance, generate income and maintain capital. These findings highlight the importance of continuous efforts to improve bank health and performance in the face of changing market dynamics